Cardiac CT Imaging Diagnosis of Cardiovascular Disease - Budoff, Matthew J.; Shinbane, Jerold S. (Springer London : Imprint: Springer, 2010)
The comprehensive assessment of cardiovascular structure and function with computed tomography (CT) has progressed at an astounding rate due to advances in scanning technology and image processing. Given the growing importance of cardiovascular CT, this book collates all relevant imaging findings and presents them in a clinically relevant and practical manner appropriate for the spectrum of physicians who diagnose and treat cardiovascular disease. The chapters have been written by an internationally renowned group of contributing authors and present discussion and images which characterize the full spectrum of cardiovascular CT.